The versatile device with MoTe2 mode-locker for ultrafast optics application. (March 2021) - Han, X.X.; Wang, X.F.; Huang, T.C.; Yan, X.A.
Highlights: A versatile device with the function of optical coupler, isolator, WDM, and mode-locker. A new method of incorporating two-dimensional materials into ultrafast system, such as MoTe2 . Improvement of the environmental stability for two-dimensional materials based mode locker, such as MoTe2 . A simplified laser with the advantage of miniaturization. Abstract: The widespread applications of ultrafast fiber lasers in various fields are due to their inherent advantages of compact configuration, excellent pulse quality, and extraordinary stability. The combination of optical passive device and two-dimensional materials is a promising approach of improving the fiber laser's performance. Here, we demonstrate a versatile optical device with MoTe2 mode-locker and a simplified ultrafast laser based on the proposed device. The proposed device can greatly improve the environmental stability of two-dimensional MoTe2 mode-locker, and provide a new method of incorporating two-dimensional materials into ultrafast optics application. The versatile device with MoTe2 mode-locker has important application in ultrafast fiber laser. The simplified laser has great commercial value in various fields like optical communication, optical sensing, and materials processing.